RADI-03. A strategy to personalize the use of radiation in patients with brain metastasis based on S100A9-mediated resistance. (9th August 2021) - Miarka, Lauritz; Moteiro, Catia; Dalmasso, Celine; Fustero-Torre, Coral; Yebra, Natalia; Hegarty, Aisling; Keelan, Stephen; Goy, Yvonne; Mohme, Malte; Caleiras, Eduardo; Damir, Vareslija; Young, Leonie; et al.
Abstract: Finding effective treatment options for patients with brain metastasis remains an unmet need. Given the limitations imposed by the blood-brain-barrier for systemic approaches, radiotherapy offers a superior ability to access the brain. While clinical practice recently adapted the use of stereotactic radiosurgery (SRS), Whole-Brain-Radiotherapy (WBRT) continuous to be an important treatment option, since many patients present with multifocal lesions or bad performance scores, rendering them ineligible for SRS. Unfortunately, overall survival of patients remains unaffected by radiotherapy. Despite this clinical data, the molecular mechanisms that allow metastatic cells to resist radiotherapy in the brain is unknown. We have applied WBRT to experimental brain metastasis from lung and breast adenocarcinoma and validated their resistance in vivo . An unbiased search to identify potential mediators of resistance identified the S100A9-RAGE-NFkB-JunB pathway. Targeting this pathway genetically reverts the resistance to radiotherapy and increases therapeutic benefits in vivo . In two independent cohorts of brain metastasis from lung and breast adenocarcinoma patients, levels of S100A9 correlate with the response to radiotherapy, offering a novel approach to stratify patients according to their expected benefit. In order to make this biomarker also available for brain metastasis patients receiving palliative WBRT without preceding surgery, we complemented our tumor-specimen based approach with the less invasive detection of S100A9 from liquid biopsies. Here, serum S100A9 also correlated with a worse response to WBRT in brain metastasis patients. Furthermore, we have validated the use of a blood-brain-barrier permeable RAGE inhibitor to restore radio-sensitivity in experimental brain metastasis models in vivo and in patient-derived organotypic cultures of radio-resistant brain metastasis ex vivo . In conclusion, we identified S100A9 as a major mediator of radio-resistance in brain metastasis and offer the molecular framework to personalize radiotherapy by exploiting it as a biomarker and as a therapeutic target, thus maximizing the benefits for the patient.